Polyurethane composite material as well as preparation method and application thereof
By adding glass fiber and a variety of specifications of magnetic powder to the polyurethane composite material and applying a magnetic field, it has better sound absorption performance in the low frequency band, which solves the problem of insufficient sound absorption performance of existing materials in the low frequency band.
Patent Information
- Application Number
- CN202411834189.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-21
AI Technical Summary
The sound absorption performance of existing polyurethane foam plastics in the low frequency band is not ideal enough, and it is difficult to effectively reduce the low-frequency noise generated by transformers in substations.
By adding glass fibers and a variety of specifications of magnetic powder to the polyurethane composite material, and applying a magnetic field during the preparation process, the magnetic powder is distributed according to certain rules to form a local resonant structure, thereby improving the low-frequency sound absorption performance of the material.
Through the coordinated use of glass fiber and magnetic powder, the channel structure and local resonance frequency in polyurethane materials are changed, which significantly improves the low-frequency noise reduction performance of composite materials.
Smart Images

Figure BDA0005186269760000071 
Figure BDA0005186269760000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of noise reduction, in particular to a polyurethane composite material and a preparation method and application thereof. Background Art
[0002] In recent years, noise pollution from substations has become a growing focus of attention. The largest noise source in a substation is the transformer, which consists of two parts: transformer noise and auxiliary cooling device noise. The main noise includes noise generated by the core, winding, oil tank (including magnetic shielding, etc.), and the cooling device noise includes fan and oil pump noise. The former is high-frequency noise, and the latter is low-frequency noise. Low-frequency noise is different from high-frequency noise. Low-frequency noise decreases slowly, and the sound waves are longer, so it can easily pass through obstacles, run long distances, and penetrate walls directly into the human ear. Since low-frequency noise can reach the human ear bone directly, living in a low-frequency noise environment of a certain intensity for a long time can cause sympathetic nerve tension, tachycardia, high blood pressure, and endocrine disorders. People who are forced to accept this noise are prone to annoyance, excitement, irritability, and even loss of reason. If you are harassed by low-frequency noise for a long time, it is easy to cause neurasthenia, insomnia, headaches, and other neuroses, and even affect the fetus in the belly of pregnant women, causing fetal malformations. Living in such noise for a long time has a great impact on people's hearing and nervous system, and it is an organic and irreversible change. Generally speaking, the elderly and people with chronic diseases and sensitive constitutions are more susceptible to the harm of low-frequency noise.
[0003] The traditional way of controlling noise is mainly aimed at medium-frequency and high-frequency noise, but the effect is not obvious compared to the low-frequency noise of the control transformer. Polyurethane foam plastic is a widely used acoustic material. It not only has the damping sound absorption mechanism of flexible materials, but also has the sound absorption mechanism of porous materials. It has good sound absorption performance in the medium and high frequency bands, but its sound absorption performance in the low frequency band is still not ideal. Therefore, it is necessary to further modify and study polyurethane foam to improve its low-frequency sound absorption coefficient. In the prior art, the controllable space for improving low-frequency sound absorption performance by simply changing the structural ratio of the material itself is limited.
[0004] Therefore, a polyurethane composite material that can improve low-frequency sound absorption performance has broad application prospects. Summary of the invention
[0005] Based on this, the purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a polyurethane composite material that can improve the low-frequency sound absorption performance and a preparation method and application thereof.
[0006] To achieve the above object, the technical solution adopted by the present invention is: a polyurethane composite material, comprising the following components in parts by weight: 100 parts of polyether polyol, 50-80 parts of diphenylmethane diisocyanate, 1-3 parts of dimethyl silicone oil, 30-40 parts of glass fiber, 200-400 parts of magnetic powder, and 3-10 parts of deionized water;
[0007] The magnetic powder is composed of four specifications of magnetic powder, namely A, B, C and D. The mesh number of specification A is D1, and specification A is 500 mesh <D1≤1000 mesh magnetic powder; the mesh number of specification B is D2, and specification B is 250 mesh <D2≤500 mesh magnetic powder; the mesh number of specification C is D3, and specification C is 150 mesh <D3≤250 mesh magnetic powder; the mesh number of specification D is D4, and specification D is 80 mesh <D4≤150 mesh magnetic powder.
[0008] Glass fiber can change the pore structure in polyurethane materials, enhance the mechanical properties of polyurethane, and can also achieve noise reduction by dissipating sound energy through fiber vibration. Magnetic powder can be distributed in the composite material according to a certain rule to form a local resonance structure, which can effectively absorb sound energy and further improve the low-frequency noise reduction performance of the composite material. The present invention uses glass fiber and magnetic powder in a coordinated manner to synergistically change the pore structure in the polyurethane material and change the local resonance frequency, so that the sound absorption performance of the composite material is further improved.
[0009] Preferably, the number average molecular weight of the polyether polyol is 1000-5000; the number average molecular weight of the dimethyl silicone oil is 2000-5000.
[0010] Preferably, the weight ratio of the magnetic powders of the four specifications A, B, C, and D is specification A: specification B: specification C: specification D = (4-5): (3-3.5): (2-2.5): 1. Further preferably, the weight ratio of the magnetic powders of the four specifications A, B, C, and D is specification A: specification B: specification C: specification D = 4:3:2.5:1.
[0011] The inventors found in actual experiments that when magnetic powder is selected into four specifications of A, B, C, and D, magnetic powders of different mesh sizes are stratified, and the magnetic powders from small to large are regularly stratified in the material, which better changes the pore structure in the polyurethane material, thereby changing the local resonance frequency and further improving the sound absorption performance of the composite material.
[0012] Preferably, the weight ratio of the glass fiber to the magnetic powder is 1:(7-12).
[0013] The inventors found in actual experiments that the weight ratio of glass fiber to magnetic powder further affects the pore structure and local resonance frequency in the polyurethane material, thereby affecting the sound absorption performance of the composite material. When the weight ratio of glass fiber to magnetic powder is 1: (7-12), the sound absorption performance is better.
[0014] Preferably, the glass fibers are chopped glass fibers, and the diameter of the chopped glass fibers is 9-15 μm and the length is 3-6 mm.
[0015] Optionally, the diameter of the chopped glass fibers is measured using an optical microscope, and the length is measured using a vernier caliper.
[0016] In addition, the present invention provides a method for preparing the polyurethane composite material, comprising the following steps:
[0017] (1) Weighing polyether polyol and diphenylmethane diisocyanate according to the above weight parts, and keeping them warm in a water bath for later use;
[0018] (2) Weighing dimethyl silicone oil, glass fiber, and deionized water according to the above weight parts, adding the polyether polyol insulated in a water bath in step (1), adding a catalyst and then ultrasonically dispersing to obtain a mixture A; adding magnetic powder weighed according to the above weight parts to obtain a mixture B;
[0019] (3) adding the diphenylmethane diisocyanate in the water bath in step (1) to the mixture B, stirring and mixing, pouring into a mold, applying a magnetic field to generate a foaming reaction, and obtaining a mixture C;
[0020] (4) The mixture C is taken out after free maturation to obtain the polyurethane composite material.
[0021] Preferably, the catalyst is at least one of triethylenediamine and dibutyltin dilaurate, and the amount of the catalyst used is 0.5%-3% of the mass of the polyether polyol.
[0022] Preferably, in the step (1), the water bath insulation temperature is 40-75°C; in the step (2), the ultrasonic dispersion power is 20-450kHz, and the time is 0.5-2.5h; in the step (3), the stirring time is 10-25s, the rotation speed is 1100-1400r / min, and the foaming time is 7-15min; in the step (4), the free maturation time is 10-24h.
[0023] Preferably, in step (3), in step (3), the initial magnetic field strength is 5-10mT, and the magnetic field strength increases with the foaming time, increasing by 1-15mT per minute; preferably, the magnetic field strength increases in stages with the foaming time t, specifically as follows: in the first stage 0≤t≤2min, the magnetic field strength increases by 1-2mT per minute; in the second stage 2<t≤5min, the magnetic field strength increases by 3-5mT per minute; in the third stage 5<t≤8min, the magnetic field strength increases by 8-10mT per minute; in the fourth stage 8<t≤15min, the magnetic field strength increases by 12-15mT per minute.
[0024] In the preparation process of the polyurethane composite material of the present invention, a magnetic field is applied during the reaction process, and the magnetic field is used to arrange magnetic powder regularly in the material. Magnetic powders of different mesh sizes are adsorbed by magnetic force and are layered. Magnetic powders from small to large are regularly layered in the material, which changes the pore structure in the polyurethane material and the local resonance frequency, so that the sound absorption performance of the composite material is further improved.
[0025] Furthermore, the present invention provides application of the polyurethane composite material in acoustic materials; alternatively, the present invention provides application of the polyurethane composite material in sound-absorbing materials.
[0026] Compared with the prior art, the beneficial effects of the present invention are as follows: glass fiber can change the pore structure in the polyurethane material, enhance the mechanical properties of the polyurethane, and can also dissipate sound energy through fiber vibration to achieve a noise reduction effect. Magnetic powder can be distributed in the composite material according to a certain rule to form a local resonance structure, which can effectively absorb sound energy and further improve the low-frequency noise reduction performance of the composite material. The present invention uses glass fiber and magnetic powder in a coordinated manner to synergistically change the pore structure in the polyurethane material and change the local resonance frequency, thereby further improving the sound absorption performance of the composite material. DETAILED DESCRIPTION
[0027] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. In the embodiments, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.
[0028] The raw materials used in the embodiments and comparative examples are described below, but are not limited to these materials:
[0029] Magnetic powder of specification A: Lingshou County Jiashuo Building Materials Processing Co., Ltd., 800 mesh;
[0030] Magnetic powder of specification B: Lingshou County Jiashuo Building Materials Processing Co., Ltd., 325 mesh;
[0031] Magnetic powder of specification C: Lingshou County Jiashuo Building Materials Processing Co., Ltd., 200 mesh;
[0032] Magnetic powder of specification D: Lingshou County Jiashuo Building Materials Processing Co., Ltd., 100 mesh;
[0033] Polyether polyol: 230, Chuangyu Chemical, molecular weight 3000;
[0034] Diphenylmethane diisocyanate: MDI, Hubei Kewode Chemical Co., Ltd., industrial grade;
[0035] Catalyst: triethylenediamine, D0493, Anaiji Chemical;
[0036] Dimethyl silicone oil: brand 201, Shandong Shuntai New Materials Co., Ltd., molecular weight 3800;
[0037] Glass fiber: Haoda chopped glass fiber, diameter 9-13μm, length 3mm, Jushi Company.
[0038] Examples and Comparative Examples
[0039] Example 1
[0040] The components and weight proportions of the polyurethane composite material of the present invention are shown in Table 1. The preparation method of the polyurethane composite material of the present invention comprises the following steps:
[0041] (1) Weighing polyether polyol and diphenylmethane diisocyanate by weight, and keeping them warm in a water bath for later use; the water bath temperature is 60° C.;
[0042] (2) Weighing dimethyl silicone oil, glass fiber, and deionized water according to the above weight parts, adding the polyether polyol in the water bath in step (1), adding a catalyst (accounting for 2% of the weight of the polyether polyol) and then ultrasonically dispersing to obtain a mixture A, adding magnetic powder weighed according to weight parts to obtain a mixture B; the ultrasonic dispersion power is 200 kHz, and the time is 2.5 hours;
[0043] (3) adding the diphenylmethane diisocyanate in the water bath in step (1) to the mixture B, stirring and mixing, and then pouring into a mold, applying a magnetic field to produce a foaming reaction, and obtaining a mixture C; the stirring time is 10 s, the rotation speed is 1200 r / min, and the foaming time is 10 min; the initial magnetic field strength is 5 mT, and the magnetic field strength increases with the foaming time, increasing by 5 mT per minute, and the magnetic field is applied for 15 minutes;
[0044] (4) The mixture C is taken out after being aged for 24 hours to obtain the polyurethane composite material.
[0045] Embodiment 2-5
[0046] The components and weight proportions of the polyurethane composite material of the present invention are shown in Table 1, except that the weight proportions of the glass fiber and the magnetic powder are different. The preparation method is exactly the same as that of Example 1.
[0047] Example 6
[0048] The components and weight proportions of the polyurethane composite material of the present invention are shown in Table 1, except that the weight proportions of diphenylmethane diisocyanate and silicone oil are different. The preparation method is exactly the same as that of Example 1.
[0049] Embodiment 7-9
[0050] The components and weight proportions of the polyurethane composite material of the present invention are shown in Table 1. Only the specifications of the magnetic powder are different. The preparation method is exactly the same as that of Example 1.
[0051] Example 10
[0052] The components and weight ratios of the polyurethane composite material of the present invention are exactly the same as those in Example 1. Only step (3) in the preparation method of the polyurethane composite material is different from that in Example 1, which is as follows:
[0053] (3) adding the diphenylmethane diisocyanate in the water bath in step (1) to the mixture B, stirring and mixing, and then pouring into a mold, applying a magnetic field to produce a foaming reaction, and obtaining a mixture C; the stirring time is 10 s, the rotation speed is 1200 r / min, and the foaming time is 10 min; the initial magnetic field strength is 10 mT, and the magnetic field strength increases with the foaming time, increasing by 10 mT per minute, and the magnetic field is applied for 15 minutes;
[0054] Embodiment 11
[0055] The components and weight ratios of the polyurethane composite material of the present invention are exactly the same as those in Example 1. Only step (3) in the preparation method of the polyurethane composite material is different from that in Example 1, which is as follows:
[0056] (3) adding the diphenylmethane diisocyanate in the water bath in step (1) to the mixture B, stirring and mixing, pouring into a mold, applying a magnetic field to produce a foaming reaction, and obtaining a mixture C; the stirring time is 10 s, the rotation speed is 1200 r / min, and the foaming time is 10 min; the magnetic field strength increases in stages with the foaming time t, as follows: in the first stage, 0≤t≤2min, the magnetic field strength increases by 1mT per minute; in the second stage, 2<t≤5min, the magnetic field strength increases by 3mT per minute; in the third stage, 5<t≤8min, the magnetic field strength increases by 10mT per minute; in the fourth stage, 8<t≤15min, the magnetic field strength increases by 12mT per minute;
[0057] Example 12
[0058] The components and weight ratios of the polyurethane composite material of the present invention are exactly the same as those in Example 1. Only step (3) in the preparation method of the polyurethane composite material is different from that in Example 1, which is as follows:
[0059] (3) adding the diphenylmethane diisocyanate in the water bath in step (1) to the mixture B, stirring and mixing, pouring into a mold, applying a magnetic field to produce a foaming reaction, and obtaining a mixture C; the stirring time is 10 s, the rotation speed is 1200 r / min, and the foaming time is 10 min; the magnetic field strength increases in stages with the foaming time t, as follows: in the first stage, 0≤t≤2min, the magnetic field strength increases by 2mT per minute; in the second stage, 2<t≤5min, the magnetic field strength increases by 5mT per minute; in the third stage, 5<t≤8min, the magnetic field strength increases by 8mT per minute; in the fourth stage, 8<t≤15min, the magnetic field strength increases by 15mT per minute;
[0060] Comparative Example 1
[0061] The polyurethane composite material of the present invention has the same weight selection and preparation method as Example 1, except for the magnetic powder specifications, and includes the following components in weight: 100 parts of polyether polyol, 60 parts of diphenylmethane diisocyanate, 2 parts of silicone oil, 30 parts of glass fiber, 250 parts of magnetic powder, and 8 parts of deionized water; wherein the magnetic powder is composed of three kinds of specifications of magnetic powder, A, B, and C, with specification A: specification B: specification C = 4:2:1.
[0062] Comparative Example 2
[0063] The polyurethane composite material of the present invention has the same weight selection and preparation method as Example 1, except for the magnetic powder specifications, and includes the following components in weight: 100 parts of polyether polyol, 60 parts of diphenylmethane diisocyanate, 2 parts of silicone oil, 30 parts of glass fiber, 250 parts of magnetic powder, and 8 parts of deionized water; wherein the magnetic powder is composed of three specifications of magnetic powder: B, C, and D, with specification B: specification C: specification D = 4:2:1.
[0064] Comparative Example 3
[0065] The polyurethane composite material of the present invention has the same weight selection and preparation method as Example 1, except for the magnetic powder specifications, and includes the following components in weight: 100 parts of polyether polyol, 60 parts of diphenylmethane diisocyanate, 2 parts of silicone oil, 30 parts of glass fiber, 250 parts of magnetic powder, and 8 parts of deionized water; wherein the magnetic powder is composed of two specifications of magnetic powder, B and C, with specification B: specification C = 4:2.
[0066] Comparative Example 4
[0067] Compared with Example 1, the polyurethane composite material of the present invention only does not contain glass fiber, and includes the following components in parts by weight: 100 parts of polyether polyol, 60 parts of diphenylmethane diisocyanate, 2 parts of silicone oil, 250 parts of magnetic powder, and 8 parts of deionized water; the weight ratio of the four specifications of magnetic powder is specification A: specification B: specification C: specification D = 4:3:2.5:1.
[0068] Comparative Example 5
[0069] The polyurethane composite material of the present invention does not contain magnetic powder and comprises the following components in parts by weight: 100 parts of polyether polyol, 60 parts of diphenylmethane diisocyanate, 2 parts of silicone oil, 30 parts of glass fiber and 8 parts of deionized water.
[0070] Table 1
[0071]
[0072] Performance Testing
[0073] According to GB / T 18696.2-2002, the sound absorption coefficient and acoustic impedance of the acoustic impedance tube are measured. The polyurethane composite materials prepared in the examples and comparative examples are tested.
[0074] The test results are shown in Table 2.
[0075] Table 2
[0076]
[0077] As can be seen from the above table, the polyurethane composite material prepared by the present invention, through the coordinated use of glass fiber and magnetic powder, synergistically changes the pore structure in the polyurethane material and changes the local resonance frequency, and the 4000Hz sound absorption coefficient is above 0.8, so that the sound absorption performance of the composite material is further improved.
[0078] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A polyurethane composite material, characterized in that: The invention comprises the following components in parts by weight: 100 parts of polyether polyol, 50-80 parts of diphenylmethane diisocyanate, 1-3 parts of dimethyl silicone oil, 30-40 parts of glass fiber, 200-400 parts of magnetic powder, and 3-10 parts of deionized water; The magnetic powder is composed of four specifications of magnetic powder, namely A, B, C and D. The mesh number of specification A is D1, and specification A is 500 mesh <D1≤1000 mesh magnetic powder; the mesh number of specification B is D2, and specification B is 250 mesh <D2≤500 mesh magnetic powder; the mesh number of specification C is D3, and specification C is 150 mesh <D3≤250 mesh magnetic powder; the mesh number of specification D is D4, and specification D is 80 mesh <D4≤150 mesh magnetic powder.
2. The polyurethane composite material according to claim 1, characterized in that: The weight ratio of the magnetic powders of the four specifications A, B, C and D is specification A: specification B: specification C: specification D = (4-5): (3-3.5): (2-2.5):
1.
3. The polyurethane composite material according to claim 1, characterized in that: The weight ratio of the magnetic powders of the four specifications A, B, C and D is specification A: specification B: specification C: specification D = 4:3:2.5:
1.
4. The polyurethane composite material according to claim 1, characterized in that: The weight ratio of the glass fiber to the magnetic powder is 1:(7-12).
5. The polyurethane composite material according to claim 1, characterized in that: The glass fibers are chopped glass fibers, and the diameter of the chopped glass fibers is 9-15 μm and the length is 3-6 mm.
6. A method for preparing the polyurethane composite material according to any one of claims 1 to 5, characterized in that: The steps include: (1) Weighing polyether polyol and diphenylmethane diisocyanate according to the above weight parts, and keeping them warm in a water bath for later use; (2) Weighing dimethyl silicone oil, glass fiber, and deionized water according to the above weight parts, adding the polyether polyol insulated in a water bath in step (1), adding a catalyst and then ultrasonically dispersing to obtain a mixture A; adding magnetic powder weighed according to the above weight parts to obtain a mixture B; (3) adding the diphenylmethane diisocyanate in the water bath in step (1) to the mixture B, stirring and mixing, pouring into a mold, applying a magnetic field to generate a foaming reaction, and obtaining a mixture C; (4) The mixture C is taken out after free maturation to obtain the polyurethane composite material.
7. The method for preparing the polyurethane composite material according to claim 6, characterized in that: In the step (1), the water bath temperature is 40-75°C; in the step (2), the ultrasonic dispersion power is 20-450kHz, and the time is 0.5-2.5h; in the step (3), the stirring time is 10-25s, the rotation speed is 1100-1400r / min, and the foaming time is 7-15min; in the step (4), the free maturation time is 10-24h.
8. The method for preparing the polyurethane composite material according to claim 6, characterized in that: In the step (3), the magnetic field strength is initially 5-10mT, and the magnetic field strength increases with the foaming time, increasing by 1-15mT per minute; preferably, the magnetic field strength increases in stages with the foaming time t, specifically as follows: in the first stage 0≤t≤2min, the magnetic field strength increases by 1-2mT per minute; in the second stage 2<t≤5min, the magnetic field strength increases by 3-5mT per minute; in the third stage 5<t≤8min, the magnetic field strength increases by 8-10mT per minute; in the fourth stage 8<t≤15min, the magnetic field strength increases by 12-15mT per minute.
9. Use of the polyurethane composite material according to any one of claims 1 to 5 in acoustic materials.